Simulative predictions and analysis of vehicle dynamical responses. (2015) - Desai, Manan; Channiwala, S.A.; Nagarsheth, H.J.
The dynamics of a vehicle and its mechanistic understanding has always been a critical area of research for dynamicists and manufacturers in the automotive industry. Designing a vehicle system from the riding comfort and stability perspectives, necessitates development of 'self-formulating' (Wahage, 1987) computer models capable of numerically simulating a broad range of vehicular configurations and real life driving situations for response predictions. The paper delineates development of one such simulative model of a quarter of the vehicle and its subsequent implementation in MATLAB/Simulink for dynamical response predictions. The parametric studies subsequent to analytical and experimental qualifications revealed the model to be sensitive to vehicle configurations and suspension features, over and above driving speed and road terrain roughness. The model was employed further for subjective evaluation of riding comfort as codified by ISO2631 international standards under a variety of driving situations. The proposed model, with appropriate treatment could be employed to diagnose, analyse and optimise the critical dynamical attributes right at the design stage, eliminating the need of expensive prototype building and time consuming testing procedures.